Tracing the Three Atlantic Branches Entering the Arctic Ocean With 129I and 236U. Issue 9 (25th September 2018) - Casacuberta, N.; Christl, M.; Vockenhuber, C.; Wefing, A.‐M.; Wacker, L.; Masqué, P.; Synal, H.‐A.; Rutgers van der Loeff, M.
Abstract: This study presents the data on 129 I and 236 U concentrations in seawater samples and sea ice cores obtained during two expeditions to the Arctic Ocean that took place onboard R/V Polarstern (PS94) and R/V Lance (N‐ICE2015) in summer 2015. Carbon‐14 was also measured in the deep water samples from the Nansen, Amundsen, and Makarov Basins. The main goal was to investigate the distribution of 129 I and 236 U in a transect from the Norwegian Coast to the Makarov Basin to fully exploit the potential of combining 129 I and 236 U as a dual tracer to track Atlantic waters throughout the Arctic Ocean. The use of the 129 I/ 236 U and 236 U/ 238 U atom ratios allowed identifying a third Atlantic branch that enters the Arctic Ocean (the Arctic Shelf Break Branch) following the Norwegian Coastal Current that carries a larger proportion of the European reprocessing plants signal compared to Fram Strait Branch Water and Barents Sea Branch Water. The combination of 129 I and 236 U also allowed quantifying the different proportions of the La Hague stream, the Scottish stream, and Atlantic waters forming the three Atlantic branches of the Arctic Ocean Boundary Current. The results show that the 129 I/ 236 U atom ratio can now be used to identify the different Atlantic branches entering the Arctic Ocean. New input functions for 129 I, 236 U, and 129 I/ 236 U have also been described for each branch, which can be further used for calculation of transit time distributions of Atlantic waters. Plain Language Summary: In this work we present results of artificial radionuclides that were measured in seawater samples collected in the Arctic Ocean. We measured the long‐lived artificial radionuclides 129 I and 236 U to track the different water masses. These two radionuclides are present in the marine environment after the nuclear weapon tests (1950s–1960s) and from two European nuclear reprocessing plants (from 1960s until today) located in France and United Kingdom. In particular, the input of 129 I from these two reprocessing plants changed over time and can therefore also be used to estimate travel times of water masses. In this study, we collected about 150 seawater samples from 20 different stations in the Arctic Ocean in summer 2015, onboard the R/V Polarstern . Our results reveal that the mixing ratios of the two reprocessing plant effluents are different for the Fram Strait Branch and the Barents Sea Branch, contrasting with previous studies. The 129 I/ 236 U was used as a new tool to identify the characteristics of these two Atlantic branches entering the Arctic Ocean and even prove the existance of a more surface branch (Arctic Shelf Break Branch) carrying a significant proportion of reprocessing plant‐derived radionuclides. Key Points: The 129 I/ 236 U ratio can be used to identify Fram Strait Branch Waters (FSBW) from Barents Sea Branch Waters (BSBW) in the central Arctic Ocean The high 129 I/ 236 U atom ratio (> 400) allowed identifying a third branch of Atlantic Waters entering the Arctic Ocean New input functions of 129 I, 236 U, and 129 I/ 236 U for the three Atlantic branches entering into the Arctic Ocean are defined